Controladoria empresarial : gestão econômica para as micro e pequenas empresas. - Monteiro, José Morais (2010)
This study aims to identify the importance of Corporate Controller for the universe of small businesses, as regards the applicability of their tools to improve the process of management. For that was selected micro and small enterprises in the cities of Aracaju and Nossa Senhora do Socorro in Sergipe, in 2009.The methodological procedures applied in the selection of companies have followed the criteria of convenience, using the inductive method, using the application of a questionnaire to managers/owners of the forty selected micro and small businesses who were willing to answer questions. Are presented in this paper some concepts collected from references consolidated in specific books Controller, forming the theoretical basis for comparative work in the same line of observation and the present investigation, adding to the reader more insight into the subject. Possession of the consolidation of the results showed that the tools of the Controller Enterprise (planning, budgeting, financial analysis, information management) are not fully utilized by micro and small companies surveyed - even taking into account constraints on composition and size of those organizations - towards better and efficient results, corroborated with the findings of the authors of similar studies, referenced in this dissertation. However, it is shown that micro and small businesses already have a more integrated vision of what the management and the need for information so that the goals are achieved more consistently and with minimum risk of business. For this, the perception of this evolution is apparent when the managers interviewed said the need to expand knowledge of strategy, controls, financial and managerial accounting, with the specific purpose of taking hands reasons to decide the direction of the enterprise. Thus, consolidates the need to manage micro and small enterprises with professionalism, aimed at reducing the death business segment, since the representation in the economic and social development is considerable, taking into account the contribution of 20 % to GDP (IBGE, 2005) and by volume of 91% of formal employment that is generated by the segment (BNDES, 2005).